Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Calculate the differentiation
Answer
circle-check-icon
expand-arrow-icon
Graph
$y = 3 x - 1$
$x$-intercept
$\left ( \dfrac { 1 } { 3 } , 0 \right )$
$y$-intercept
$\left ( 0 , - 1 \right )$
$y = 3x-1$
$x = \dfrac { 1 } { 3 } y + \dfrac { 1 } { 3 }$
$ $ Solve a solution to $ x$
$y = \color{#FF6800}{ 3 } \color{#FF6800}{ x } - 1$
$ $ Move $ x $ term to the left side and change the sign $ $
$y \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = - 1$
$\color{#FF6800}{ y } - 3 x = - 1$
$ $ Move the rest of the expression except $ x $ term to the right side and replace the sign $ $
$- 3 x = - 1 \color{#FF6800}{ - } \color{#FF6800}{ y }$
$- 3 x = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ y }$
$ $ Organize the expression $ $
$- 3 x = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$ $ Change the sign of both sides of the equation $ $
$3 x = y + 1$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
$ $ Divide both sides by the same number $ $
$\color{#FF6800}{ x } = \left ( \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 3 }$
$x = \left ( y + 1 \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 3 }$
$ $ Convert division to multiplication $ $
$x = \left ( y + 1 \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$x = \left ( \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$ $ Multiply each term in parentheses by $ \dfrac { 1 } { 3 }$
$x = \color{#FF6800}{ \dfrac { 1 } { 3 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$\dfrac {d } {d x } {\left( y \right)} = 3$
Calculate the differentiation of the logarithmic function
$\dfrac {d } {d \color{#FF6800}{ x } } {\left( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right)}$
$ $ Calculate the differentiation $ $
$\color{#FF6800}{ 3 }$
$ $ 그래프 보기 $ $
Linear function
Solution search results
search-thumbnail-$9\right)$ O Select the function that matches the graph. 
$y$ 
$5$ 
$\bar{-5} $ $\bar{5} $ $x$ 
$-5$ 
$y=3x-1$ $y=3x^{2}+1$ $y=3x$ $y=3x+1$
7th-9th grade
Algebra
search-thumbnail-If you are making table ofvalue, just substitute the x value to get y 
$y=3x-1$ 
-2 -1 1. 2. 

Solution Since y = f(x), to get the values of y and complete the table we need to do this x y 
$1rx=-2$ $irx=-1$ if x=0 
$y=3x-1$ $y=3x-1$ $y=3x-1$ 
$f\left(x\right)=3x-1$ $f\left(x\right)=3x-1$ $f\left(x\right)=3x-1$ 
$f\left(-2\right)=3\left(-2\right)-1$ $f\left(-1\right)=3\left(-1\right)-1$ $f\left(0\right)=2\left(0\right)-1$ 
$f\left(-2\right)=-6-1$ $f\left(-1\right)=-3-1$ $f\left(0\right)=0-1$ 
$f\left(-2\right)=-7$ $f\left(-1\right)=-4$ $f\left(0\right)=-1$ then, 
y = -7 then, y = -4 then, y = -1
1st-6th grade
Other
search-thumbnail-$|y=x-1$ 
y $=3x+1$
7th-9th grade
Other
search-thumbnail-$1\right)$ O Select the function that matches the graph. 
$y$ 
$5$ 
$\bar{-5} $ $5$ $x$ 
$-5$ 
$y=3x-1$ $y=3x^{2}+1$ $y=3x$ $y=3x+1$
10th-13th grade
Other
search-thumbnail-$3$ $y=3x-1$ 
$y=-2x+1$ 
$\left(1.2\right)$
7th-9th grade
Other
Have you found the solution you wanted?
Try again
Try more features at QANDA!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo